Pengaruh Ajaran Neng-Ning-Nung-Nang dan Religiusitas terhadap Niat Mahasiswa Melakukan Pinjaman Online - Wardani, Dewi Kusuma; Djumaati, Musyrifah (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this research is to determine the influence of neng-ning-nung-nang teachings and religiosity on students' intentions to take online loans. This research is quantitative by utilizing primary data. A total of 110 respondents were selected in this study using snowball sampling techniques, where questionnaires were sent using Google Form. This research data was processed using SPSS. The results of this study found that neng-ning-nung-nang teachings and religiosity had a negative effect on students' intentions to take online loans